Guideline concordance and antibiotic-associated adverse events between Veterans administration and non-Veterans administration dental settings: a retrospective cohort study - Ramanathan, Swetha; Evans, Charlesnika T.; Hershow, Ronald C.; Calip, Gregory S.; Rowan, Susan; Hubbard, Colin; Suda, Katie J. (Frontiers in Pharmacology, 2024)
Background. Antibiotics prescribed as infection prophylaxis prior to dental procedures have the potential for serious adverse drug events (ADEs). However, the extent to which guideline concordance and different dental settings are associated with ADEs from antibiotic prophylaxis is unknown. Aim. The purpose was to assess guideline concordance and antibiotic-associated ADEs and whether it differs by VA and non-VA settings. Methods. Retrospective cohort study of antibiotic prophylaxis prescribed to adults with cardiac conditions or prosthetic joints from 2015-2017. Multivariable logistic regression models were fit to assess the impact of ADEs, guideline concordance and dental setting. An interaction term of concordance and dental setting evaluated whether the relationship between ADEs and concordance differed by setting. Results. From 2015-2017, 61,124 patients with antibiotic prophylaxis were identified with 62 (0.1%) having an ADE. Of those with guideline concordance, 18 (0.09%) had an ADE while 44 (0.1%) of those with a discordant antibiotic had an ADE (unadjusted OR: 0.84, 95% CI:0.49-1.45). Adjusted analyses showed that guideline concordance was not associated with ADEs (OR: 0.78, 95% CI: 0.25-2.46), and this relationship did not differ by dental setting (Wald χ^2 p-value for interaction=0.601). Conclusions. Antibiotic-associated ADEs did not differ by setting or guideline concordance.